The entrepreneur is dead – long live the static-hedonic! Guiding principles and economic concepts of a degrowth society - Ötsch, Silke (Momentum Quarterly, 2016)
Authors sometimes condense analysis on societal change into ideal types, such as the worker, the capitalist, the engineer, the bureaucrat, the entrepreneur, etc. This is coupled with problem diagnosis and assumptions about an optimum configuration of the economy and society. With recent environmental scenarios expecting serious threats for humanity and nature, new ideal types might emerge. Ideas related to Joseph Schumpeter’s ideal type of the entrepreneur are little contested and can be found in recent debates. They justify strategies like the Green Economy. Schumpeter used the ideal type of the ‘static-hedonic’ person or economy as a negative counterpart of the entrepreneur. It seems that recently the degrowth and urban gardening movements are rediscovering qualities of the static-hedonic economy and society as valuable. Based on qualitative problem-oriented interviews with persons engaged within the Transition movement, I analyse their concepts of provisioning. Does the gardener represent a new ideal type and concepts of provisioning that replace Schumpeter’s ideal type of the entrepreneur?